Analysis of science process skills in physics education students - Maison Maison; Darmaji Darmaji; Dwi Agus Kurniawan; Astalini Astalini; Utari Prisma Dewi; Lia Kartina (Graduate School, Universitas Negeri Yogyakarta, 2019)
This study aims to analyze students' science process skills on specific heat material by reviewing two aspects of basic science process skills indicators (observation and classification), and two indicators of integrated science process skills (identifying variables and making hypotheses). This research uses a descriptive quantitative method. In this study, the sample used was 35 students of physics education of batch 2018 who were randomly selected. The assessment instrument used was the science process skills observation sheet with the skill score used in the form of a Likert scale. The results of the study show that the students' mastery of basic science process skills on the observation indicator is 65% in the good category, 30% in the high category, and 10% in the category of not good to low, whereas, the classification indicators obtained are 54.3% and 37.1% of students have mastered classification skills in both good and high categories. The remaining 8.6% are classified in the not good category. For the mastery of integrated science process skills in the variable identification indicator, 60% of them are in the good category and 14.3% in the high category. The rest are in the category of not good and low. For the indicators of skills in making hypotheses, 65.7% and 14.3% are in the good and high categories. It proves that physics education students have mastery of science process skills that are in the good category.